Synthesis, Crystal Structures, and Properties of Zeolite‐Like T3(H3O)2[M(CN)6]2·uH2O (T = Co, Zn; M = Ru, Os). Issue 23 (20th June 2017) - Reguera, Leslie; López, Noeldris L.; Rodríguez‐Hernández, Joelis; González, Marlene; Hernandez‐Tamargo, Carlos E.; Santos‐Carballal, David; de Leeuw, Nora H.; Reguera, Edilso
Abstract : We report the synthesis, crystal structures, and related properties of six new zeolite‐like hexacyanometallates of formula unit T3 (H3 O)2 [M(CN)6 ]2 · u H2 O (T = Co 2+, Zn 2+ ; M = Ru II, Os II ). Their crystal structures were solved and refined from their X‐ray powder diffraction patterns in combination with the IR and UV/Vis/NIR spectroscopic data. The Co and Zn ions are coordinated tetrahedrally to the N atoms of four CN groups. The deconvolution of the overlapped UV/Vis/NIR spectral bands provided conclusive evidence of the tetrahedral coordination of the Co atoms. These materials have porous frameworks, which are characterized by a 3D array of TN4 tetrahedral units linked to the MC6 octahedral blocks in a 3:2 ratio. From the IR spectroscopy results, we found that all of the compounds reported here contain hydronium countercations. Two different structures in the same space group ( R 3 c ) were identified for the Co‐based materials. However, only a single phase was found for the Zn‐containing compounds. Density functional theory (DFT) modeling predicts hydrogen bonds between the hydronium ions and the CN groups at the surfaces of the pores. These materials were prepared through the hydrothermal recrystallization of the solids obtained from mixing ethanol solutions of H4 [M(CN)6 ] with aqueous solutions of cobalt(II) nitrate and zinc nitrate. Our results illustrate the potential of the hydrothermal recrystallization technique for the preparation of metal hexacyanometallates with new structures and pore topologies that are not obtainable by the traditional precipitation method. Abstract : Six zeolite‐like hexacyanometallates of formula T3 (H3 O)2 [M(CN)6 ]2· u H2 O (T = Co 2+, Zn 2+ ; M = Ru II, Os II ) are synthesized, and their crystal structures are solved from their powder XRD patterns in combination with IR and UV/Vis spectroscopic data. The H2 isotherms provide an indication of the effective polarizing power of the hydronium ion.